The Influence of FOMO (Fear of Missing Out) and Marketplace Gamification on Gen Z's Financial Behavior with Self-Control as a Moderator - Lita Ningrum Afriani; Rofi Puspitaningtias; Gita Rahmadani (CV Edujavare Publishing, 2026)
The increasing use of digital platforms among Gen Z has contributed to the emergence of consumptive behaviors driven by various digital stimuli, including limited-time notifications, reward systems, and game-based features designed to enhance user engagement. This study aims to analyze the influence of Fear of Missing Out (FOMO) and marketplace gamification features on impulsive financial behavior among Generation Z, with self-control acting as a moderating variable. Unlike previous studies that examined FOMO and gamification separately, this research integrates both variables into a single model to provide a more comprehensive explanation of Generation Z’s financial behavior by combining psychological factors and digital design elements. Using a quantitative approach, data were collected through questionnaires distributed to 100 Generation Z respondents who actively use marketplaces, selected through purposive sampling. The data were analyzed using Multiple Linear Regression Analysis with SMART PLS 3. The findings reveal that Fear of Missing Out (FOMO) does not significantly affect financial behavior, whereas gamification has a significant influence on financial behavior. Furthermore, self-control strengthens the relationship between gamification and financial behavior but does not moderate the relationship between FOMO and financial behavior. This study is limited to Generation Z marketplace users, which restricts the generalization of findings to other age groups or digital platform users. Nevertheless, the results provide valuable insights for marketplace practitioners, policymakers, and academics in developing strategies to enhance digital financial literacy, design more responsible gamification features, and strengthen self-control mechanisms to promote healthier financial behavior in the digital era.